PERANCANGAN BUSINESS TO BUSINESS PADA TOKO TUNAS BARU SIMPANG PINOH - Okta Saputra; Sandy Kosasi (P3M STMIK Profesional Makassar, 2023)
The Tunas Baru store has challenges in service both conventionally and via Whatsapp. The owner only employs two employees so resellers have to queue. In addition, the large number of orders via WhatsApp makes it difficult for owners to reply to chats one by one and prepare orders so that mistakes can occur in preparing orders. The purpose of this study is to design a B2B website at the Tunas Baru store to ease the work of the owners and employees, make it easier to order goods and save time on sales transactions at the Tunas Baru store. This research is in the form of a case study with a research method using Design Science Research (DSR). The development method uses Rapid Application Development (RAD). The programming languages ​​used are PHP, Javascript, HTML and MySOL database server. The system modeling uses UML (Unified Modeling Language). This research produces a B2B website at the Tunas Baru store that can be used by owners to manage product data, display sales reports, manage product stock, view payments, view orders and manage users level. Then the resellers can search and order goods through the website. In addition, website users can register to become a resellers of the Tunas Baru store